Changes in Lipoproteins Associated With Methotrexate or Combination Therapy in Early Rheumatoid Arthritis: Results From the Treatment of Early Rheumatoid Arthritis Trial. Issue 6 (30th May 2013) - Navarro‐Millán, Iris; Charles‐Schoeman, Christina; Yang, Shuo; Bathon, Joan M.; Bridges, S. Louis; Chen, Lang; Cofield, Stacey S.; Dell'Italia, Louis J.; Moreland, Larry W.; O'Dell, James R.; Paulus, Harold E.; Curtis, Jeffrey R.
<x xml:space="preserve">Abstract</x> Objective To study changes in lipid profiles at 24 weeks among patients with early rheumatoid arthritis (RA) participating in the Treatment of Early RA (TEAR) trial and randomized to receive methotrexate (MTX) plus etanercept, triple therapy (MTX plus sulfasalazine plus hydroxychloroquine), or aggressively titrated MTX monotherapy. Methods This TEAR substudy included 459 participants with biologic specimens. Serum levels of total cholesterol, low‐density lipoprotein (LDL) cholesterol, and high‐density lipoprotein (HDL) cholesterol were measured at 0 and 24 weeks. Results At 24 weeks, there were statistically significant increases in mean cholesterol levels in the MTX plus etanercept, triple therapy, and MTX monotherapy arms. The observed increases were 31.4 mg/dl, 28.7 mg/dl, and 30 mg/dl in LDL cholesterol, 19.3 mg/dl, 22.3 mg/dl, and 20.6 mg/dl in HDL cholesterol, and 56.8 mg/dl, 53 mg/dl, and 57.3 mg/dl in total cholesterol (P < 0.0001 versus baseline for each comparison). There was a statistically significant decrease in the ratio of total cholesterol to HDL cholesterol at 24 weeks in all 3 treatment groups versus baseline. There was no difference in any lipid changes between the 3 treatment arms. After multivariable adjustment, change in C‐reactive protein, but not the Disease Activity Score in 28 joints, was associated with change in LDL cholesterol (P = 0.03) and total cholesterol (P = 0.01). Baseline glucocorticoid use was associated with changes in HDL cholesterol (P = 0.03) and total cholesterol (P = 0.02). Conclusion Levels of total cholesterol, LDL cholesterol, and HDL cholesterol increased comparably shortly after initiation of MTX plus etanercept, triple therapy, and MTX monotherapy among patients with early RA with active disease participating in a clinical trial. The clinical relevance of short‐term changes in traditional lipids on cardiovascular outcomes remains to be determined.